ANALISIS PENGARUH BUDAYA ORGANISASI DAN DUKUNGAN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan bagian antaran PT. Pos Indonesia Processing Center Semarang) - Wijaya, Nina Ariani; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2017)
This study aims to analyze the impact of organizational culture and organizational support toward organizational citizenship behavior (OCB) with organizational commitment as an intervenning variable. The result’s differences among past researches and the upgrade of the law no. 38 of 2009 relating to the postal matter indicate the need to improve the performance and the quality of human resources of PT. Pos Indonesia Semarang. This study uses two independent variables and one intervenning variable. This study aims to examine and analyze the effect of organizational culture and organizational support on organizational citizenship behavior (OCB), with organizational commitment as intervening variable.Data collection methods used in this study are questionnaires using census method, with the respondents of all the employees from the delivery section of PT. Pos Indonesia (Persero) Central Processing Unit Semarang, and the statistical analysis by using SPSS. This study uses data analysis methods include validity test, reliability test, classic assumption test, multiple linear regression analysis, path analysis, sobel test, coefficient determination test, F test and t test.The result show that the effect value of organizational culture and organizational support toward organizational citizenship behavior with organizational commitment as intervening variable equal to 48,64% While 31,16% is explained by the factors out of the variable. From the result of Multiple Regression Analysis analysis of organizational culture and organizational support have a positive impact toward organizational commitment and organizational culture, organizational support and organizational commitment have a positive impact toward organizational citizenship behavior.